Lessons learned on the design and the conduct of European Post Authorisation Safety Studies (PASS) : review of 3 years of PRAC oversight - Almas, Mariana Ferreira Baltazar de Matos (2017)
Tese de mestrado, Epidemiologia, Universidade de Lisboa, Faculdade de Medicina, 2017